2017
DOI: 10.1039/c7cc00718c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalysed intramolecular carbenoid insertion of α-diazo-α-(methoxycarbonyl)acetanilides for oxindole synthesis

Abstract: A novel, selective palladium-catalysed carbenoid C(aryl)-H insertion of α-diazo-α-(methoxycarbonyl)acetanilides leading to oxindoles is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…We also explored the palladium‐catalyzed carbene C–H insertion of α‐diazo‐α‐(methoxycarbonyl)acetanilides. We found that when using palladium catalysts the C–H insertion of such amides occurs selectively into the arylic Csp 2 –H to give the oxindole …”
Section: Introductionmentioning
confidence: 99%
“…We also explored the palladium‐catalyzed carbene C–H insertion of α‐diazo‐α‐(methoxycarbonyl)acetanilides. We found that when using palladium catalysts the C–H insertion of such amides occurs selectively into the arylic Csp 2 –H to give the oxindole …”
Section: Introductionmentioning
confidence: 99%
“…To this end, we first explored the process involving 1 a , which, in the presence of [{Pd(IMes)(NQ)} 2 ], led to the formation of tetrahydroquinoline 2 a (Table , entry 2). Similar to related Pd 0 ‐mediated C−H insertions of α‐diazocarbonyl compounds, our calculations started from the corresponding pallada(0)–carbene intermediate INT0 , formed by the reaction of diazo compound 1 a and a model Pd 0 catalyst in which the bulky mesyl groups in the N‐heterocyclic carbene (NHC) ligand were replaced by phenyl groups. This species evolves into the seven‐membered palladacycle INT1 via transition state TS1 in a highly exergonic transformation (Δ G R =−25.3 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The examples in Ta bles1and 2, below,c onfirm the generality and functional group tolerance of these reactions. As observed in Ta ble 1, no competition from sp 3 -CÀHi nsertion was observed upon startingf rom para-a nd meta-substituted N-isopropylanilines ( meta-Substituted anilines 1e-i also underwent chemoselective sp 2 -C Ar ÀHf unctionalization to give the corresponding tetrahydroquinolines with either the Pd 0 or Ru-1 catalysts;t he latter once again afforded the highest reaction yields ( Table 1, entries [15][16][17][18][19][20][21][22][23][24][25]. With these substrates, the regioselectivity of insertion( 5-X/7-X ratio) seems to be controlled by ac ombination of steric and electronic effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations